Retrospective Analysis of Hemorrhage After Pediatric Tonsillectomy - Nuri Ünsal; Esma Hande Baldır; Serap Bulut Çöbden; Yunus Kantekin; Altan Kaya; Mehmet Yaşar; İbrahim Özcan; Ali Bayram (Turkish Archives of Otorhinolaryngology, 2025)
Objective: This study was conducted to retrospectively analyze pediatric tonsillectomy in patients aged <18 years treated over the past five years, focusing on factors such as sex, surgical method, season of occurrence, transfusion requirement, and surgical intervention in patients presenting with post-tonsillectomy hemorrhage. Methods: Tonsillectomies performed in the Otorhinolaryngology Clinic of the Kayseri City Training and Research Hospital between June 2019 and June 2024 were retrospectively analyzed using the hospital information management system. Patients re-admitted for post-tonsillectomy secondary hemorrhage were identified, including those managed conservatively, requiring surgical intervention, and/or needing blood transfusion. Hemorrhage incidents were categorized by season (warm: March-August; cold: September-February), and hemorrhage rates were calculated. Surgical methods and the first surgical techniques in patients presenting with hemorrhage were recorded. Results: In total, 4,994 tonsillectomies had been performed in the study period. Sixty patients (1.20%) were re-admitted and hospitalized due to postoperative hemorrhage, of whom 22 (0.44%) were reoperated and 38 (0.76%) were managed conservatively. Ten patients (0.20%) needed transfusion. Of the patients presenting with hemorrhage, 39 (65%) were admitted during the warm season, and 21 (35%) during the cold season. The cold dissection technique was used in 95.03% of the cases, with a hemorrhage rate of 1.2%. Conclusion: Tonsillectomy is a common procedure worldwide and post-tonsillectomy hemorrhages are a frequent complication. Reducing morbidity and mortality through preventive strategies is crucial. Patients presenting with post-tonsillectomy hemorrhage should be hospitalized, monitored closely, and evaluated with hemogram and coagulation tests to assess hemorrhage volume and transfusion needs.